Emergent informal use of doxycycline post- and pre-exposure prophylaxis among men who have sex with men and transgender and gender diverse people, the Netherlands, 2024 - Vita W Jongen (Eurosurveillance, 2025)
BACKGROUND Doxycycline post-exposure and pre-exposure prophylaxis (doxyPEP/PrEP) to prevent sexually transmitted infections (STIs) is not part of standard practice in the Netherlands but may be used informally (without prescription). AIM We assessed informal use and intention to use doxyPEP/PrEP among men who have sex with men (MSM) and transgender and gender diverse people in the Netherlands. METHODS Between 26 February and 6 May 2024, we conducted an online survey on informal doxyPEP/PrEP use in the preceding 6 months and intention to use. We assessed the determinants of recent informal use and high intention to use using risk ratio regression. RESULTS Of the 1,633 participating individuals (96.7% MSM) 246 (15%) reported doxyPEP/PrEP use in the preceding 6 months. Informal use was more common among participants who used HIV PrEP or were living with HIV, had ≥ 15 anonymous sexual partners, engaged in chemsex, wanted to protect themselves, got advice from others to use doxyPEP/PrEP and believed doxyPEP/PrEP is safe. High intention to use (n = 1,063 (65%) participants) was more common among participants using HIV PrEP or living with HIV, who wanted to have condomless sex, who wanted to protect others from STIs and who perceived doxyPEP/PrEP as effective and safe. CONCLUSION Although doxyPEP/PrEP is not formally recommended in the Netherlands, survey participants reported informal use and a high intention to use. These findings, combined with the global increase of antimicrobial resistance (AMR), stress the need for close monitoring and further research on the AMR effects of doxyPEP/PrEP use.